Clinical research A case series: Egyptian experience in using chemical pleurodesis as an alternative management in refractory hepatic hydrothorax - Helmy, Nariman; Akl, Yosri; Kaddah, Safy; Abd El Hafiz, Hamed; El Makhzangy, Hisham (Archives of Medical Science, 2010)
Introduction: Chemical pleurodesis is an effective treatment for malignant effusion and pneumothorax. Although this mode of therapy is less widely accepted in treatment of patients with hepatic hydrothorax, the need for palliative treatment in such patients encouraged us to do this work. The aim of study was analysing the outcome of chemical pleurodesis using bovoiodine, Vibramycin and talc slurry in treatment of hepatic hydrothorax. Material and methods: A case series randomized study including 23 patients with symptomatic right side hepatic hydrothorax not responding to medical treatment and repeated thoracocentesis was conducted. From March 2007 to March 2008, 19 men and 4 women with a mean age of 54.3 ±8.1 years (range 42-70 years) underwent medical thoracoscopies to achieve pleurodesis by application of 3 sclerosing agents. Results: Out of the 23 patients pleurodesis was repeated in 20 cases. Three cases did not attend their follow-up so their responses to pleurodesis are not known. The follow-up period of the study was 3 months. The procedure was effective in 15 of 20 patients (75%): 7/8 cases treated with bovoiodine (87.5%), and 4/6 cases with Vibramycin and talc slurry (66.7%) for each. There were 4 recurrences (20%) and a single case of mortality (5%) due to hepatic coma which can be attributed to the course of the disease. We detected minimal morbidity during the follow-up period of 3 months. Conclusions: The procedure appears to be indicated for these fragile patients especially when medical therapy fails. Chemical pleurodesis deserves to be considered as an alterative therapy in such patients.